Early identification of macrophage activation syndrome in adult-onset Still’s disease: a case report and literature review - Long, Ting; Xu, Jing; Lin, Bo-Zhi; Li, Sheng-Guang (Frontiers in Medicine, 2025)
BackgroundAdult-onset Still’s disease (AOSD) is a rare systemic inflammatory disorder characterized by high spiking fevers, evanescent rash, and polyarthritis. A serious complication of AOSD is macrophage activation syndrome (MAS), a life-threatening hyperinflammatory condition that can lead to multiorgan failure if not promptly diagnosed and treated.ObjectiveThis case report and literature review focus on the early identification of MAS in patients with AOSD, highlighting diagnostic challenges, differential diagnoses, and the utility of scoring systems like the HScore and MS score in clinical practice.Case presentationWe report the case of an 80-year-old woman who presented with a complex diagnostic challenge involving AOSD complicated by MAS and concurrent cytomegalovirus (CMV) infection. Her clinical course was marked by recurrent high fevers, cytopenias, hyperferritinemia, and liver dysfunction. Despite extensive workup, initial diagnoses of infections and autoimmune conditions were considered and ruled out. The HScore and MS score were calculated to be 210 and 1.607, respectively, both indicative of MAS. The patient was treated according to the HLH-94 protocol, with high-dose dexamethasone and etoposide, alongside broad-spectrum antimicrobial and antiviral therapy. She responded well to treatment, with resolution of fever and improvement in clinical symptoms.DiscussionThe overlap between AOSD and MAS symptoms complicates early diagnosis, making scoring systems critical in differentiating MAS from other conditions. The HScore and MS score provided a structured approach to diagnosis, guiding timely intervention and improving the patient’s prognosis. Our literature review emphasizes the importance of early recognition and integration of these scoring systems into routine clinical practice to enhance outcomes.ConclusionThis case underscores the necessity of early identification and intervention in MAS associated with AOSD. The application of diagnostic scoring systems like the HScore and MS score is essential for prompt diagnosis and effective treatment, ultimately improving patient survival rates.